Teaching styles and sports engagement: mediation by satisfaction and resilience in Chinese adolescents - Liepeng Huang; Fengjuan Tian; Fengjuan Tian; Furong Li (Frontiers in Psychology)
PurposeThis study examined the associations between perceived PE teacher teaching styles on Chinese middle school students' sports learning engagement, and the mediating roles of classroom satisfaction and psychological resilience.MethodsA cross-sectional survey assessed 1,629 junior and senior high school students in Chengdu and Chongqing, Validated scales measured perceived teaching styles, psychological resilience, sports learning engagement, and PE class satisfaction. SPSS 26.0 was used for correlation, regression, and mediation analyses (SPSS PROCESS v4.1 Macro, Model 4).ResultsPerceived teaching styles were positively associated with sports learning engagement (β = 0.371, 95%CI = 0.343–0.398, p < 0.01). Significant associations emerged for rigorous-logical (β = 0.292, 95%CI = 0.066–0.518, p < 0.05), caring-sharing (β = 0.489, 95%CI = 0.179–0.800, p < 0.01), and innovative-exploratory (β = 0.898, 95% CI = 0.523–1.273, p < 0.01) styles, but not for humorous-active (β = 0.095, 95% CI = −0.092–0.282, p > 0.05).Classroom satisfaction and psychological resilience partially mediated the relationship between teaching style and learning engagement (p < 0.05), with the mediating role of psychological resilience (26.0%) being significantly stronger than that of classroom satisfaction (18.9%).ConclusionThere is a significant positive association between PE teachers‘ teaching styles and students' PE learning engagement. Moreover, classroom satisfaction and psychological resilience play mediating roles in this relationship. Therefore, it is recommended that PE teachers prioritize the adoption of positive teaching styles in PE classroom instruction.